Overview on the Development of Aquaculture and Aquafeed Production in Korea - Kim, Sung-Sam; Kim, Jeong Dae (Aquacultura Indonesiana, 2019)
Total landings of capture and culture fisheries in Korea increased from 1,073,000 metric tons (MT) in 1971 to 3,743,000 MT in 2017 mainly due to the development in marine aquaculture practices. During last four decades, marine aquaculture production in Korea showed around 5-fold increase from 491,000 MT in 1977 to 2,310,000 MT in 2017 recording the value of 2.9 billion USD. Last year, the main production was derived from seaweed (1,755,630 MT), while the aquatic animal production was made from shellfish (428,160 MT), fish (86,400 MT), crustacean (mainly shrimp of 5,100 MT) and others (34,530 MT). Inland aquaculture is based on fish farming with the production of around 25,000 MT. Either trash fish or moist pellet based on the raw fish is still being fed to marine culture fish, which is the main obstacle for developing the farming. In 2017, around 450,000 MT of trash fish with 87,980 MT of extruded pellets were employed to produce 86,399 MT of marine fish.